Breakfast consumption habit and its impact on nutrient intake and nutritional status of medical undergraduates - Mathiyalagen, Prakash; Yadav, Dhananjay; R, Anandaraj; Vasudevan, Kavita; Sundar, Buvaneshwari; R, Priyadharsini; Mishra, Meerambika; Jin, Jun-O (Progress in Nutrition, 2019)
Aim: Breakfast is considered the most important meal of the day, the quality and quantity of which potentially contributes to the total daily energy and nutritional well-being of an individual. Gluttony, sedentary lifestyle and obesity are common among the breakfast skippers. Among numerous lifestyle factors contributing to overweight in youth, skipping breakfast has been identified as a potential risk factor but with controversial results. Hence, this study was aimed to investigate the impact of breakfast skipping habit among the undergraduate students with nutrient intake and nutritional status. Material and methods: This cross-sectional study was conducted among undergraduates studying in a medical college of Puducherry. 274 students who agreed to participate filled a pre-tested semi-structured questionnaire having a dietary record over 3 consecutive days including Sunday. Standard WHO (World Health Organization) techniques and guidelines for anthropometric measurements and BMI classification and ICMR (Indian Council of Medical Research) dietary guidelines to calculate calorific values of food items was used. Chi-square test, Student’s t test and Mann-Whitney U test was used and p value <0.05 was considered statistically significant. Results: 60% and 24% of the students reported skipping breakfast at least once/week and thrice/week respectively. Body mass index was significantly higher among those who skipped breakfast more than thrice per week. 44%, 35% and 24% were overweight and obese among those who skipped breakfast more than thrice/week, at least once/week and never skipped respectively. Breakfast skippers had higher fat intake, lower intake of proteins, vitamins and minerals than breakfast consumers. Busy schedule and lack of appetite in the morning were common reasons reported by breakfast skippers. Conclusion: This study suggests that there is a possible relationship between breakfast skipping with overweight and faulty nutrient intake. Health promotion activities for healthy eating behaviors among youths are recommended in order to prevent lifestyle diseases and create a healthy role models for tomorrow.